Novice Learner In-Plane Ultrasound Imaging: Which Visualization Technique?. Issue 4 (1st July 2013) - Speer, Melanie; McLennan, Neil; Nixon, Chris
Abstract : Background and Objectives: Needle guidance under ultrasound is an acquired skill requiring fine motor control. Maintaining the image of an advancing needle in the plane of an ultrasound beam may be performed with the probe and needle orientated along the visual axis (AL) or across the visual axis (AC). This study was undertaken to determine if orientation affected task performance. Methods: Twenty-four relative novices were tasked to perform guided punctures to a target in a pork phantom using each technique 5 times. The technique first used was randomly chosen from a sealed envelope. The time taken to guide the needle to target and the accuracy of needle imaging were recorded. Results: The mean time to locate the target was significantly faster for the AL technique, compared with the AC technique (group AL, 35.7, vs group AC, 58.6 seconds; P < 0.0001, Wilcoxon matched-pairs signed rank test). The mean imaging quality score was also significantly better when needle advancement was along the visual axis (group AL, 1.37, vs group AC, 1.64; P = 0.05). Conclusions: Advancing the needle along the visual axis was associated with improved task completion speed and quality of needle imaging. This ergonomic pattern, therefore, may be the more appropriate choice for novices learning ultrasound-guided in-plane needle imaging.